Incidence of Head injuries at District Barkhan Baluchistan - MUHAMMED AZAM KHETRAN, SAMINA REHMAN (Journal of Fatima Jinnah Medical University, 2018)
Objective: The purpose of this study was to find out the incidence of head injury resulting from assault conducted at the DHQ Hospital Barkhan during period of three years. Subjects and Method: A retrospective study of 211 cases of head injury resulting from assault was conducted at the DHQ Hospital Barkhan during period of three years (Jan 2009 to Dec 2011). Result: Total no of cases were 211, among these 123 cases proved to be fatal while 88 cases survived. Among the fatal cases, firearms were the most common assault weapon, were used in 37% (n=78) of cases followed by blunt instruments 27% (n=58). Sharp weapons were the least common weapon used in 20% (n=20). The multiple cranial bone fracture was detected in skull examination. Conclusion: Fatality among attack victims with firearm injuries to the head is very high. The location of meningeal haemorrhage whether in single or multiple layers has little influence on the outcome while haemorrhage in the deeper layers has higher fatality. Thus these may be considered as high risk factors in violent attacks to the head.